2024
DOI: 10.1007/978-3-031-45679-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Rural NEETs: Pathways Through Formal and Non-formal Education

Paul Flynn,
Heidi Paabort,
Valentina Milenkova
et al.

Abstract: Formal and non-formal education often constitute the first line of engagement in supporting Rural young people Not in Employment, nor in Education, or Training (NEET). However, it is not always the case that such interventions are widely documented. This chapter aims to uncover best practice interventions for the educational inclusion of rural NEETs building upon an emergent body of work in order to frame the identification of five case studies across Estonia, Italy, Latvia, Albania, Portugal. EU and non-EU me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These non-transition rates are reflected in other European countries such as Portugal, Spain, and Italy. Estonia and Bosnia and Herzegovina, particularly in rural areas where young people who exit the formal education system early often fall into the precarity a Not in Employment, Education or Training (NEET) status [13,14]. A target transition rate of 54% is set for the duration of the National Access Plan: A Strategic Action Plan for Equity of Access, Participation and Success in Higher Education 2022-2028 [9], an objective of approximately two percentage points each year.…”
Section: Irish Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-transition rates are reflected in other European countries such as Portugal, Spain, and Italy. Estonia and Bosnia and Herzegovina, particularly in rural areas where young people who exit the formal education system early often fall into the precarity a Not in Employment, Education or Training (NEET) status [13,14]. A target transition rate of 54% is set for the duration of the National Access Plan: A Strategic Action Plan for Equity of Access, Participation and Success in Higher Education 2022-2028 [9], an objective of approximately two percentage points each year.…”
Section: Irish Contextmentioning
confidence: 99%
“…Sci. 2024, 14, 341 2 of 13 Moreover, in a comprehensive survey of US science graduates, while over half reported that their interest in science developed before or during primary/elementary school, around a third nevertheless reported that their interest developed during secondary school [3]. Determining the primary factors influencing students' intentions or choices remains challenging.…”
Section: Introduction 1intention To Study Science At Upper Secondary ...mentioning
confidence: 99%